ANALISIS PERENCANAAN PPH PASAL 21 UNTUK MEMINIMALKAN BEBAN PAJAK KLIEN - Budhi Purwantoro Jati; Sapto Bayu Aji; Evi Grediani; Rahmawati Hanny Yustrianthe (Universitas Riau Kepulauan, 2023)
This study was conducted to compare the calculation of Article 21 income tax using the nett method, gross method, and gross-up method on KJA Eko Darmawan in planning Article 21 income tax to minimize the tax burden of its clients. This research uses a comparative descriptive approach by collecting data from Eko Darmawan Accounting Services Firm and analyzing tax planning strategies implemented in case studies of the firm's clients. The results of the study can be concluded that the researcher proposed an efficient gross-up method in minimizing the client's tax burden.